A Promoter Polymorphism in the CD59 Complement Regulatory Protein Gene in Donor Lungs Correlates With a Higher Risk for Chronic Rejection After Lung Transplantation. Issue 3 (30th October 2015) - Budding, K.; van de Graaf, E. A.; Kardol‐Hoefnagel, T.; Broen, J. C. A.; Kwakkel‐van Erp, J. M.; Oudijk, E.‐J. D.; van Kessel, D. A.; Hack, C. E.; Otten, H. G.
ABSTRACT: Complement activation leads primarily to membrane attack complex formation and subsequent target cell lysis. Protection against self‐damage is regulated by complement regulatory proteins, including CD46, CD55, and CD59. Within their promoter regions, single‐nucleotide polymorphisms (SNPs) are present that could influence transcription. We analyzed these SNPs and investigated their influence on protein expression levels. A single SNP configuration in the promoter region of CD59 was found correlating with lower CD59 expression on lung endothelial cells (p = 0.016) and monocytes (p = 0.013). Lung endothelial cells with this SNP configuration secreted more profibrotic cytokine IL‐6 (p = 0.047) and fibroblast growth factor β (p = 0.036) on exposure to sublytic complement activation than cells with the opposing configuration, whereas monocytes were more susceptible to antibody‐mediated complement lysis (p < 0.0001). Analysis of 137 lung transplant donors indicated that this CD5 9 SNP configuration correlates with impaired long‐term survival (p = 0.094) and a significantly higher incidence of bronchiolitis obliterans syndrome (p = 0.046) in the recipient. These findings support a role for complement in the pathogenesis of this posttransplant complication and are the first to show a deleterious association of a donor CD59 promoter polymorphism in lung transplantation. Abstract : In this study, the authors show both a functional relation between a single promotor polymorphism in the CD59 gene, protein expression, and susceptibility to complement‐mediated cell lysis, as well as a clinical relation of this genetic configuration in the donor and the risk for development of obstructive chronic lung allograft dysfunction in the recipient after lung transplantation.